Collecting the spat of scallop Mizuhopecten yessoensis in conditions of associated settling of pacific mussel Mytilus trossulus - Galina S. Gavrilova; Elena S. Kondratieva (Известия ТИНРО, 2017)
Collecting the spat of good quality and enough quantity, as the seeding material for commercial cultivation of scallop Mizuhopecten yessoensis Jay, 1857, is one of the main problems for aquaculture farms in Primorye. In the eastern Ussuri Bay, pacific mussel Mytilus trossulus Gould, 1850 is the dominant species which larvae settle on the systems designed for the scallop spat collecting. Its spat quantity in collectors exceeds the scallop spat number in 5-65 times, with the biomass in 3-140 times higher. The scallop spat survival dependence on abundance of the mussel spat is investigated but any correlation is not detected. However, general quality of the scallop spat in the farms in the Ussuri Bay is poor that could be a reason of its low survival on further stages of cultivation: mean size of the scallop spat here is close to the lower acceptable limit of the standard range (10-11 mm). Besides, food resources for the scallop spat could be limited in the years with high abundance of the mussel spat.